(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the use of stylistic devices in advertising language, emphasizing their crucial role in enhancing the effectiveness of marketing campaigns. It discusses a variety of rhetorical techniques such as metaphor, alliteration, hyperbole, and rhetorical questions, explaining how each device serves to grab attention, engage emotions, and influence consumer behavior. Through examples from well-known brands like Nike, Coca-Cola, and M&M’s, the article illustrates how these devices create memorable and persuasive messages. The piece concludes by highlighting the importance of stylistic devices in building brand identity and fostering emotional connections with consumers, ultimately ensuring the success of advertising efforts in a competitive market. This overview provides valuable insights for those interested in understanding the language of advertising and its psychological impact on audiences.